Photo report on climate smart livestock feed and forage Innovations​ trainings - Seifu, Haimanot (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation in Training Workshop on Climate Smart Livestock Feed and Forage Innovations. Addis Ababa, Ethiopia.